Irrigation pocket book, or, Facts, figures, and formulae, for irrigation engineers being a series of notes on miscellaneous subjects connected with irrigation - Buckley, Robert Burton, 1847-1927 (F. N. Spon, 1928)
This book is simply a compilation of facts, figures and formulae bearing on the everyday work of an irrigation engineer. It has its origins in the author's peronal notebooks from 33 years' work in India.